2002
DOI: 10.1097/00006676-200205000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Atrophy in Experimental Severe Acute Pancreatitis

Abstract: These results indicate that splenic atrophy resulting from splenocyte reduction occurs in rat experimental severe acute pancreatitis. It is suggested that splenocytes are recruited into systemic circulation in response to peripheral lymphocyte reduction as a result of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…We have successfully reproduced this animal model in previous studies [18] . Researchers have used this model to evaluate immunoinflammatory response related to severe acute pancreatitis [6,16,21] . In the present study, the IL-2, IL-10, and IFN-␥ productivity was measured in ConA-stimulated splenocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have successfully reproduced this animal model in previous studies [18] . Researchers have used this model to evaluate immunoinflammatory response related to severe acute pancreatitis [6,16,21] . In the present study, the IL-2, IL-10, and IFN-␥ productivity was measured in ConA-stimulated splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Yasuda et al [16] reported that, in severe acute pancreatitis, splenic atrophy occurred as a result of reduction in splenocytes which indicated an impairment of the cellular immunity. Moreover, Curley et al [17] demonstrated a diminished production of interleukin (IL)-2 by splenocytes isolated from mice with severe acute pancrea titis.…”
Section: Introductionmentioning
confidence: 99%
“…Differently from the thymus, however, no apoptosis was detected in the splenocytes from the rats with pancreatitis. 46 Peripheral lymphocytes in the rats with pancreatitis were significantly decreased due to apoptosis compared with those in sham-operated rats. With antecedent splenectomy, peripheral lymphocyte counts were significantly lower than those in rats without splenectomy.…”
Section: Apoptosis Of Lymphocytes and Lymphatic Tissuesmentioning
confidence: 92%
“…46 In splenocytes harvested 24 h after the induction of pancreatitis, proliferative activity was lowered, and IL-2 secretion in response to concanavalin A was also depressed. The results obtained suggested that the Th1/Th2 balance tended toward Th1 suppression as a whole in severe pancreatitis.…”
Section: Apoptosis Of Lymphocytes and Lymphatic Tissuesmentioning
confidence: 98%
“…Particularly, Curley et al reported a significant decrease in the proportion of helper T cells in severe acute pancreatitis. 5 Moreover, we have reported that thymic atrophy and splenic atrophy occur in rat experimental severe acute pancreatitis 7,8 and that peripheral lymphocyte reduction due to apoptosis is linked to the development of subsequent infectious complications in patients with severe acute pancreatitis. 9,10 Recently, the concept of "Th1 (helper T cell type 1)/ Th2 (helper T cell type 2) balance" has been introduced for understanding the pathophysiological response during many diseases.…”
Section: Introductionmentioning
confidence: 99%